2011
DOI: 10.1242/dev.055665
|View full text |Cite
|
Sign up to set email alerts
|

Gbx2 and Fgf8 are sequentially required for formation of the midbrain-hindbrain compartment boundary

Abstract: SUMMARYIn vertebrates, the common expression border of two homeobox genes, Otx2 and Gbx2, demarcates the prospective midbrainhindbrain border (MHB) in the neural plate at the end of gastrulation. The presence of a compartment boundary at the MHB has been demonstrated, but the mechanism and timing of its formation remain unclear. We show by genetic inducible fate mapping using a Gbx2CreER knock-in mouse line that descendants of Gbx2 + cells as early as embryonic day (E) 7.5 do not cross the MHB. Without Gbx2, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 41 publications
5
50
1
Order By: Relevance
“…However, in the absence of both of these genes, MHB organiser genes remain expressed, although their expression is not restricted to the boundary, indicating that these genes are important for the spatial refinement, rather than the induction, of genes associated with the organiser (Li and Joyner, 2001;Martinez-Barbera et al, 2001). Recent work has shown that differential expression of Otx2 and Gbx2 contributes to the segregation of midbrain and hindbrain cells, yet the mechanisms by which these two genes determine the position of the boundary are unclear, particularly as they function as transcriptional repressors (Glavic et al, 2002;Sunmonu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the absence of both of these genes, MHB organiser genes remain expressed, although their expression is not restricted to the boundary, indicating that these genes are important for the spatial refinement, rather than the induction, of genes associated with the organiser (Li and Joyner, 2001;Martinez-Barbera et al, 2001). Recent work has shown that differential expression of Otx2 and Gbx2 contributes to the segregation of midbrain and hindbrain cells, yet the mechanisms by which these two genes determine the position of the boundary are unclear, particularly as they function as transcriptional repressors (Glavic et al, 2002;Sunmonu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Once induced, MHB organiser genes become interdependent through complex crossregulatory networks that stabilise and maintain the organiser (Rhinn and Brand, 2001;Wurst and Bally-Cuif, 2001). In particular, Fgf8 has been shown to be important in maintaining lineage restriction at the boundary (Sunmonu et al, 2011).…”
Section: Notch Specifies Boundary Cell Fatementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the co-repressive actions of Otx2 and Gbx2 at the boundary, Fgf8, Gbx2 and Notch signalling (Sunmonu et al, 2011;Tossell et al, 2011) promote cell sorting and, hence, lineage restriction at the boundary. The signalling molecule Fgf8 also has a key role in establishing and maintaining the cerebellar boundary.…”
Section: The Cerebellar Anlage Sits Between Hox and Otx Domainsmentioning
confidence: 99%
“…As conditional deletion using creER creates genetic mosaicism (supplementary material Fig. S2) (Chen et al, 2009;Sunmonu et al, 2011), the guidance defects in Gbx2-CKO mutants thus reflect a cell-autonomous function of Gbx2. These in vivo studies, together with the explant assays ( Fig.…”
Section: Pathfinding Defects Of Tcas and Abnormal Robo Expression In mentioning
confidence: 99%